2012
DOI: 10.5114/aoms.2012.28552
|View full text |Cite
|
Sign up to set email alerts
|

Plasma neutrophil gelatinase-associated lipocalin as an early biomarker for prediction of acute kidney injury after cardio-pulmonary bypass in pediatric cardiac surgery

Abstract: IntroductionCardiopulmonary bypass (CPB) surgery is considered one of the most frequent surgical procedures in which acute kidney injury (AKI) represents a frequent and serious complication. The aim of the present study was to evaluate the efficiency of neutrophil gelatinase-associated lipocalin (NGAL) as an early AKI biomarker after CPB in pediatric cardiac surgery.Material and methodsThe study included forty children aged 2 to 78 months undergoing CPB. They were divided into group I: patients who suffered AK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 25 publications
(32 reference statements)
2
30
2
1
Order By: Relevance
“…It is important to note that the present results do not challenge the fact that increased plasma NGAL concentration after pediatric heart surgery predicts evolving AKI (3,(16)(17)(18), although some negative findings do exist (19,20). Instead, the interpretation of the present findings offers an alternative pathophysiologic mechanism for this phenomenon.…”
Section: Discussioncontrasting
confidence: 55%
“…It is important to note that the present results do not challenge the fact that increased plasma NGAL concentration after pediatric heart surgery predicts evolving AKI (3,(16)(17)(18), although some negative findings do exist (19,20). Instead, the interpretation of the present findings offers an alternative pathophysiologic mechanism for this phenomenon.…”
Section: Discussioncontrasting
confidence: 55%
“…Haase-Fielitz et al, [88][89][90] Fadel et al, 91 and Krawczeski et al 92 have found similar results in a prospective study of adult cardiac surgery patients. In studies performed in critically ill patients with septic shock, Nickolas et al 93 found urinary NGAL to predict AKI with an AUC of 0.95.…”
Section: Neutrophil Gelatinase-associated Lipocalinsupporting
confidence: 64%
“…Both urine and plasma NGAL were powerful independent predictors of AKI, with an AUC of 0.998 for the 2-hour urine NGAL and 0.91 for the 2-hour plasma NGAL measurement. A conspicuous number of studies on NGAL for assessing AKI in the course of cardiac surgery have subsequently confirmed the results published by Mishra [114120]. In a prospective study, uNGAL was measured immediately after kidney transplantation and then for subsequent 3 times every 6 hours [121].…”
Section: Neutrophil Gelatinase-associated Lipocalin (Ngal)mentioning
confidence: 83%